Reconceptualization of the Transboundary Water Interaction Nexus (TWINS): approaches, opportunities and challenges. Issue 5 (3rd July 2020) - Grünwald, Richard; Feng, Yan; Wang, Wenling
ABSTRACT: Using a critical hydropolitics approach, we broaden the context of the Transboundary Water Interaction Nexus framework to provide a tool to analyze interstate relations on the sideline of selected water-related issues regardless of the legal status of actors; distinguish nuances between six intensities of cooperation and conflict; and simultaneously evaluate water events as a form of cooperation, conflict, or both.